2020
DOI: 10.3389/fnut.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Self-Reported Dietary Instruments Are Prone to Inaccuracies and New Approaches Are Needed

Abstract: Background: Diet is a modifiable behavior that influences an individual's health. Because of this, diet assessment is an important component of public health surveillance, evaluating response to community health interventions, and monitoring individual compliance to medical interventions. Diet assessments are usually performed using one of three basic methods: diet recall, diet diaries, or food frequency questionnaires. Although these three assessment instruments have displayed a strong agreement between thems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 38 publications
2
108
0
3
Order By: Relevance
“…We support our hypothesis that the liking survey, particularly the assessment of food and beverage liking, would add to the ability to explain levels of weight loss in response to a worksite-based intervention. Dietary assessment tools used in experimental settings may fail in community-based settings, in part, because of participant burden and misreporting [2,3]. Our findings join others [21,36,37] to support liking surveys as dietary evaluation tools.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We support our hypothesis that the liking survey, particularly the assessment of food and beverage liking, would add to the ability to explain levels of weight loss in response to a worksite-based intervention. Dietary assessment tools used in experimental settings may fail in community-based settings, in part, because of participant burden and misreporting [2,3]. Our findings join others [21,36,37] to support liking surveys as dietary evaluation tools.…”
Section: Discussionsupporting
confidence: 64%
“…However, intake misreporting, particularly in overweight and obese individuals [2], challenges linking of dietary changes with weight loss [3]. Novel methods of capturing diet behaviors for intervention studies are needed [2]. This paper extends our research on reported food/beverage liking as a novel and valid measure of dietary behaviors [4][5][6] that is feasible in workplace settings [7][8][9] as a potential tool for dietary evaluation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Assessment of individual-level misreporting compares the EI:TEE ratio to a percentage-based confidence limit (estimated using known measurement error and variance in estimated energy intake and total energy expenditure, and energy requirements). The pTEE method advocates a more stringent statistical cutoff (±1–1.5 SD) than the Goldberg method, intending to create a more biologically plausible sample where energy intake estimates are consistent with principles of energy physiology ( 18 , 53 ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, children and adolescents, like adults, may misreport their dietary intakes, either intentionally or because they are still undergoing cognitive development [ 28 ]. Several dietary recall validation studies have found children to accurately or slightly overreport their energy intakes, and younger children may report more accurately with parental assistance, but overweight or obese children and older children are more likely to underreport [ 28 , 29 ]. Third, some analyses were based on small sample sizes and may not be reliable; for example, few students attended schools that offered universal free meals.…”
Section: Discussionmentioning
confidence: 99%